Tonga : Disaster Risk Financing and Insurance - World Bank (Washington, DC, 2015)
Tonga is an archipelago composed of 172 islands spread across a combined land and sea area of 72,000sq.km. According to the 2011 census, Tonga had a population of 103, 252 people spread across 36 of the 172 islands. A population scattered so widely across such a large area can pose logistical problems for efforts to facilitate and finance disaster response. In January 2014, Tropical Cyclone Ian caused widespread damage and destruction on the Islands of Ha'apai and Vava'u. Approximately 1,094 buildings in Ha'apai were either destroyed or damaged, and some 2,335 people sought shelter in evacuation centers. There were reports of significant damage to houses, infrastructure, and agriculture across 18 villages located on the islands of Ha'apai, including Uiha, Uoleva, Lifuka, Foa, Ha'ano, and Mo'unga'one. Total ground-up loss for this event was estimated at T$90 million (US$50.3 million), of which T$20.5 million (US$11.5 million) was attributable to emergency loss (PRRAFI 2014).